Canoe (Handbook of Sports Medicine and Science, 2019)
A new volume in the Handbook of Sports Medicine and Science series from the International Olympic Committee, this volume Canoeing provides an accessible and comprehensive summary of the topic. •Provides a concise, authoritative overview of the science, medicine and psycho-social aspects of canoeing •Offers guidance on medical aspects unique to the training and coaching of canoe athletes •The only book on this subject endorsed by the Medical Commission of the International Olympic Committee (IOC) and the International Canoe Federation (ICF) •Written and edited by global thought leaders in sports medicine.